2003
DOI: 10.1007/s00147-003-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diltiazem administration and cyclosporine levels on the incidence of acute rejection in heart transplant patients

Abstract: To identify the clinical factors associated with acute rejection (AR) in the first year after heart transplantation (HT), we analysed 112 patients. All patients received OKT3 and standard triple-drug therapy. We analysed the following variables to determine their relationship with AR: age and gender, panel-reactive antibodies, HLA-DR mismatch, use of Sandimmune vs Neoral, diltiazem administration, and cyclosporine levels in week 2 and months 1, 2, and 3 after HT. Fifty-two patients had no AR and 49 had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…The mechanism has been explained by the finding that diltiazem increases the blood concentration of CyA by inhibiting CyA metabolism in hepatic cytochrome P450 enzymes [45][46][47]. However, our results showed that a Ca2 + channel blocker enhanced IL-12 p40 secretion from MDDCs.…”
Section: Discussioncontrasting
confidence: 54%
“…The mechanism has been explained by the finding that diltiazem increases the blood concentration of CyA by inhibiting CyA metabolism in hepatic cytochrome P450 enzymes [45][46][47]. However, our results showed that a Ca2 + channel blocker enhanced IL-12 p40 secretion from MDDCs.…”
Section: Discussioncontrasting
confidence: 54%
“…31 Previous studies have reported that diltiazem slows the development of CAV 32 and reduces the incidence of acute rejection. [33][34][35] Moreover, studies with heterotopic HTx models have shown that diltiazem exerts immunosuppressive and immunomodulating effects. Transmembrane calcium movement plays a critical role in lymphocyte function, and numerous investigators have demonstrated that diltiazem inhibits lymphocyte functions and depresses the immune response.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, clinical factors associated with acute rejection in the first year after heart transplantation were analyzed in 112 HTX recipients. 37 The result from this study showed that diltiazem administration and cyclosporine level in the first month after HT were both independently associated with the absence of acute rejection. Both diltiazem and cyclosporine level showed a large and independent protective effect.…”
Section: Calcium Channel Antagonistsmentioning
confidence: 61%